(untitled) (Journal of Partial Differential Equations, 1997)
In this paper, we study the general difference schemes of the boundary value problem for the nonlinear parabolic systems with two and three space dimensions. To solve the nonlinear difference schemes, we construct an iterative sequence from the solutions or the linearized difference schemes. We shall prove the convergence of the difference solutions for the iterative difference schemes to the solution of the original boundary value problem or the nonlinear parabolic systems.